2022
DOI: 10.3389/fpsyt.2022.862298
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation Among Children and Young Adults in a 24/7 Messenger-Based Psychological Chat Counseling Service

Abstract: BackgroundSuicidality in children and young adults is a pervasive problem: approximately 40% of respondents in epidemiological surveys in German schools reported suicidal ideation, while up to 9% reported a suicide attempt in the past. While there is compelling evidence for the effectiveness of telephone-based hotline services, an increasing preference of adolescents for messenger-based counseling services can be observed. Therefore, the present study aims to investigate the utilization behavior and user satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In a recent systematic review on the state of youth helplines, which is at least partly comparable to the krisenchat service, the authors concluded that helplines may provide a beneficial service to youth and that psychosocial concerns are the main reasons for contacting these services [ 45 ]. This result is in line with previous evaluations of krisenchat [ 32 , 33 ]. The authors also concluded from the results of the review that there is a lack of literature owing to a lack of controlled trials on the one hand, and complex methodological/ethical barriers preventing such trials on the other [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In a recent systematic review on the state of youth helplines, which is at least partly comparable to the krisenchat service, the authors concluded that helplines may provide a beneficial service to youth and that psychosocial concerns are the main reasons for contacting these services [ 45 ]. This result is in line with previous evaluations of krisenchat [ 32 , 33 ]. The authors also concluded from the results of the review that there is a lack of literature owing to a lack of controlled trials on the one hand, and complex methodological/ethical barriers preventing such trials on the other [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…The first cross-sectional evaluation showed a high acceptance, feasibility, and user satisfaction of this service [ 32 ]. The results indicated a high need for a 24/7 accessible, anonymous, and low-threshold online help service to offer rapid stress relief in acute crises such as suicidality [ 33 ]. Besides its goal to increase the mental health literacy of users, krisenchat aims to refer users in need to professional help services or personal contacts [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the article review show that digital health interventions that are often used to overcome suicidal ideation vary the most, namely interventions via the internet/websites in eight articles (Bailey et al, 2020;De Jaegere et al, 2019;Han et al, 2019 ;Hetrick et al, 2017;Iorfino et al, 2017;Robinson et al, 2016;Spijker et al, 2012;Sueki et al, 2014), messenger two articles (Kohls et al, 2022;Sindahl et al al., 2019), and two mobile phone applications (Rodante et al, 2022;Torok et al, 2022).…”
Section: Kinds Of Digital Health Interventionmentioning
confidence: 99%
“…Two studies used the messaging feature, or Short Messaging Service (SMS), on smartphones as a means of intervention. Among them, some use messages from social media such as WhatsApp, which is called Krisenchat (Kohls et al, 2022).…”
Section: Messengersmentioning
confidence: 99%
See 1 more Smart Citation